The impact of the Sentinel Node concept on the overall survival, disease-free survival and axillary recurrence of Breast Cancer patients - Fougo, José Luis; Dinis-Ribeiro, Mário; Dias, Teresa; Castro, Fernando; Reis, Paulo; Giesteira, Laurinda; Araújo, Cláudia (Revista Portuguesa de Cirurgia; No 24 (2013): Março 2013 - II Série, 2013)
Introduction and aims: The Sentinel Node (SN) concept emerged as a way to improve Breast Cancer (BC) staging and to reduce the morbidity of the Axillary Dissection (AD). But the influence of the SN concept on long term BC outcomes is not well defined. The aim of this work is to assess the impact of the SN concept on the overall and disease-free survival and on the axillary recurrence, in a prospectively controlled series of BC patients. Methods: This revision includes 394 consecutive BC patients, from two successive randomized clinical protocols. The first (n=166) elapsed from April 2001 to June 2003 and the second (n=228) accrued from Septem- ber 2003 to January 2005. The first study included patients with tumours less than 30mm and the pN0sn patients were randomized between AD and SN only. The second study was divided into two groups. Group A received uT1 patients; pN0sn patients were spared from the AD and pN+sn patients were submitted to AD. Group B received uT2 patients; those with pN0sn were randomized between AD and SN only. Patients were followed-up at the out-patient breast clinic, every 3 months during the first 3 years, every 6 months until 5 five years and then yearly. Events were prospectively registered in an Institutional database. Results: Median patient’s age was 55 years (range: 20-78). Median follow-up time was 66 months (range: 4-100). Two men were included. Mean overall survival time for SN only patients was 98 months and for the AD patients was 93 months (p=0.003). Mean relapse-free survival time for the SN only patients was 97 months and for the AD patients was 99 months (p-0.43). At five years of follow-up, overall survival was 98% for the SN only group and 92% for the AD group and disease-free survival was 99% for the SN only group and 100% for the AD group. There were not detected axillary nodal recurrences among SN only patients or between AD patients. Conclusions: Long-term follow-up of BC patients submitted to SN biopsy-only showed similar results to AD submitted patients, in terms of overall survival, disease-free survival and axillary node recurrence, therefore ensuring clinical long-lasting adequacy of the SN concept.  Keywords: Breast Cancer, Sentinel Node, Long-term follow-up.